Design of microchannel heat sink with wavy channel and its time-efficient optimization with combined RSM and FVM methods. (December 2016) - Zhou, Jiandong; Hatami, M.; Song, Dongxing; Jing, Dengwei
Highlights: A new wavy microchannel structure is proposed for active cooling of typical MCHS. Finite volume method (FVM) is employed to solve the governing equations. Response surface methodology (RSM) is applied to find the optimal geometry. Comprehensive heat transfer index β is used to evaluate Laminar flow heat transfer. Heat transfer for wavy microchannel is 2.8 times that of regular straight channel. Abstract: In this study, a sinusoidal wavy structure of microchannel heat sink intended for active cooling of compact electronic devices such as insulated-gate bipolar transistor (IGBT) has been designed. By combining with the finite volume method (FVM), the geometric parameter of the wavy wall, as the key factor to improve the heat transfer efficiency, has been optimized by a novel response surface methodology (RSM), which has found to be time-efficient and accurate. Furthermore, we use a comprehensive heat transfer index β to study whether the heat transfer enhancement outweighs the increased pressure drop. After investigating the Re, h, Δ P, f, β, it is concluded that the best case is occurred when wave amplitude value is 40 and wavelength is 100. For our optimized wavy channel, the heat transfer can be enhanced by a maximum of 2.8 times compared to regular straight channel. CFD simulation demonstrates that under such case, the existence and disturbance of vortex can lead to thinning of boundary layer and hence more effective heat transfer. Our results should have practical value for designing of compact heat exchanger and the proposed optimization method is supposed to have wide application for the time-efficient optimization of heat transfer through irregular configurations.